KUALITAS PERAIRAN MANGROVE DI CIASEM PAMANUKAN, KABUPATEN SUBANG, JAWA BARAT - Budi Hadi Narendra; Harris Herman Siringoringo; Andi Gustiani Salim (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
This study aimed to evaluate the water quality of mangrove ecosystem indegraded mangrove forest areas, either already or not rehabilitated. The research was conducted at the Ciasem protected forest areas, BKPH Ciasem Pamanukan (RPH Poponcol, RPH Bobos, and Tegal Tangkil RPH), Subang regency, West Java province. Observations and measurements of mangrove stands were performed using line transect and sample plots method (Line Transect Plot). Substrate and water samples were taken and analyzed in the laboratory. The results showed that the mangrove ecosystem in Subang was dominated by Avicennia sp and Rhizophora sp. Avicennia more adaptive to the shallow water, while Rhizophora more adaptive to an area closer or direct contact with the sea. Water quality conditions at the three locations were quite varied and still within the quality standard range for mangrove waters, except the BOD and DO parameters that need to be recovered because they out of the standard. Fertility conditions (physics and chemistry) of sediment (substrate) were generally in good condition for plant growth.